Investigation of ArF* excimer laser VUV radiation action on sapphire - Baschenko, S.M.; Gochelashvili, K.S.; Zakirov, R.M.; Klimov, V.I.; Mikhkelsoo, V.T.; Prokhorov, O.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Aluminium components of products escaped from the surface of a sapphire target being illuminated by VUV emission of an ArF* laser are investigated using the method of laser-induced fluorescence combined with the transient time technique. Relative concentrations of aluminium atoms and ions as well as their distribution on velocities in the flow are measured. Determined is also the temperature and velocity of aluminium atoms. It is ascertained that within the range of used energy densities of 0.45 to 1.0 J/cm² extraction of materials can be made in three regimes, namely: the ablation, the plasma and mixed ones, intertransitions between them being of a cyclic character.